MATLAB Implementation of Effects of Fifth Generation on Free Space - Haboub, Rayan Abdelazeem; Bilal, Khalid Hamid (Arab Journal for Sciences and Research Publishing, 2025)
Given that there is a widespread demand for quick internet access, all of the main telecommunications providers throughout the world are working hard to improve their speed on the internet. Internet connectivity that is dependable is becoming more in demand across the whole economy, including the home market, the watch market, the mobile phone market, and the auto-mobile market. The creation of 5G technology is a response to a society that is defined by rapidly changing conditions and increasing expectations for technological advancement. Increasing capacity, improving data rates, decreasing latency, and enhancing service quality are some of the main goals that should be pursued in the future, especially in an environment that is post-4G infrastructure. In order to accomplish these goals, the architecture of 5G cellular has to undergo substantial changes. In this research, the architecture of the 5G cellular network as well as certain breakthrough technologies that have the potential to improve the design and meet the demands of users are the primary topics of discussion and how it effects in free space.
Keywords: Mobile broadband services; latency; connectivity; throughput